Comparative Evaluation of Kedo- ‘S’square Files with Manual Instrumentation in Primary Molars: An Invitro Study: Pharmaceutical Science-Dentistry - Pragadeesh, Dr. A.P.; Prathima, Dr. G.S.; Nandakumar, Dr. S. (International Journal of Life Science and Pharma Research, 2023)
The pulpectomy procedure includes the complete removal of the pulpal tissue, debridement, and preparation of the canal space, followed by obturation. The standard method of cleaning and shaping the canals in primary teeth uses hand files, which can lead to iatrogenic errors. Kedo S files are exclusive pediatric rotary file systems of which the Kedo S Square file system (IV generation) have various advantages. The study aims to evaluate and compare the cleaning efficacy of Kedo S Square files and manual K files in root canals of primary teeth: An In-vitro comparative study was conducted, which included 56 root canals from 25 primary molars. 2-3ml of India ink dye was injected into canals and were randomly divided into two groups in which instrumentation was done using Kedo S Square files and Manual K files, respectively. The teeth were subjected to decalcification and dehydration and observed under a stereomicroscope for traces of Indian ink in the canals. Results were recorded and statistically analyzed using the Chi-Square test. Kedo S Square files had statistically better cleaning efficacy compared to the K file in the coronal(P=0.001), middle(P=0.000), and apical third(P=0.001) of the root canal. The cleaning efficacy of both Kedo S Square and K files varied in different thirds of the canals, but it was not statistically significant. Pediatric rotary Kedo S Square files were effective compared to Manual K Files concerning cleaning efficacy.